2018
DOI: 10.1038/s41598-018-35478-1
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Envelope Glycoproteins Induce the Production of TNF-α and IL-10 in Human Monocytes by Activating Calcium Pathway

Abstract: Human HIV-1 infection leads inevitably to a chronic hyper-immune-activation. However, the nature of the targeted receptors and the pathways involved remain to be fully elucidated. We demonstrate that X4-tropic gp120 induced the production of TNF-α and IL-10 by monocytes through activation of a cell membrane receptor, distinct from the CD4, CXCR4, and MR receptors. Gp120 failed to stimulate IL-10 and TNF-α production by monocytes in Ca2+ free medium. This failure was total for IL-10 and partial for TNF-α. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 87 publications
2
24
2
Order By: Relevance
“…It initiates transcription by recruiting Histone acetyltransferases to the HIV-LTR [76]. Consistent with increased transcription level, an induction of downstream proinflammatory cytokines, IL-1β, IL-6, and TNF-α was also observed during HIV-1 infection in several in vitro studies [77][78][79]. Our study also revealed that in addition to live/intact bacteria, heat-killed H. pylori can also reactivate HIV transcription.…”
Section: Discussionsupporting
confidence: 81%
“…It initiates transcription by recruiting Histone acetyltransferases to the HIV-LTR [76]. Consistent with increased transcription level, an induction of downstream proinflammatory cytokines, IL-1β, IL-6, and TNF-α was also observed during HIV-1 infection in several in vitro studies [77][78][79]. Our study also revealed that in addition to live/intact bacteria, heat-killed H. pylori can also reactivate HIV transcription.…”
Section: Discussionsupporting
confidence: 81%
“…Prolonged abnormal presence of IFN-γ reduced heme oxygenase-1 expression in human astrocytes, which contributes to oxidative stress, another pathogenic characteristic of HAND [79]. Several previous studies have found that HIV viral genes induce the expression of IL-10; however, in the Tg26 mouse model [80][81][82], we found the opposite. DHF upregulated IL-10, similar to our previous ndings in a murine model for multiple sclerosis, a neurodegenerative disease [23].…”
Section: Discussioncontrasting
confidence: 65%
“…HIV-1 gp120 and tat activate expression of proinflammatory cytokines, including tumor necrosis factor alpha [158, 159], which may stimulate EMT [97100].…”
Section: Discussionmentioning
confidence: 99%